Web-based Decision Support System for Sectorization - Ozturk, Elif Goksu; Sousa, Filipe Soares; Lima, Maria Margarida; Rodrigues, Ana Maria; Ferreira, José Soeiro; Nunes, Ana Catarina; Lopes, Isabel Cristina; Oliveira, Cristina Teles (IO 2021 - XXI Congresso da Associação Portuguesa de Investigação Operacional, 2021)
A Decision Support System (DSS) is an information system that provides computer help to decision-makers (DMs) to solve their specific problems. Under the project ‘Sectorization to Simplify and Solve (StoSS)’, we present a DSS to solve sectorization problems. Sectorization is the division of a large area, territory or network into smaller parts considering one or more objectives. The purpose of sectorization is usually to increase the efficiency and effectiveness of problem-solving. The application areas are diverse and often arise related to geographical issues. Examples include designing political districts, sales territories, school or health districting and policing zones, forest planning, waste collection or street cleaning zones and maintenance operations. Given this diversity in terms of applications, solution procedures are challenging. We design the DSS to provide solutions for various sectorization problems in a website format with a user-friendly outline. We clustered the sectorization problems into four main groups: (i) basic sectorization problems, (ii) sectorization problems with service centres, (iii) re-sectorization problems, and (iv) dynamic sectorization problems. All these groups allow the user to shape and solve the specific problem for their case.